Development of web-based ıntelligent tutoring (iTutor) to help students learn fluid statics - Kusaırı, Sentot; Kusaırı, Sentot; Alfad, Haritzah; Zulaıkah, Siti (Journal of Turkish Science Education, 2017)
Fluid statics is one of the most difficult topics for students to learn. Formative assessment and remedial instruction can help students master the concepts. However, identifying students’ challenges for formative purposes and facilitating remedial learning is not easy given to the number of students and variation of the problems encountered. An alternative solution to overcoming such problems is the use of web-based intelligent tutoring (iTutor). This research aims to develop and examine the feasibility and effectiveness of the web-based program iTutor. This research project consists of 3 steps, i.e., preliminary study, development, and examination. Three professors, 3 physics teachers, and 74 secondary students participated in this study. The instruments for collecting data included tests, questionnaires, and interviews. The questionnaire and interview data were analysed both quantitatively and qualitatively, while examination data were evaluated by means of an independent t-test. Expert judgment and trial fieldtesting data confirm the feasibility and effectiveness of using the iTutor program to improve students' mastery of physics concepts.
Keywords: formative assessment; intelligent tutoring (iTutor); remedial learning; fluid statics